Spiritual Ecology Across Faiths: A Comparative Study of GreenSufism in Indonesia and GreenFaith in the United States - Bambang Iriawan; Nurul Zahriani JF; Abdel Kadir Naffati; Ahkmad Fatoni; Yuminah Yuminah (SCAD Independent, 2026)
This comparative study examined how different religious traditions operationalize ecological values. It focused on two cases: Green Sufism, a network of pesantren (Islamic boarding schools) in Indonesia that integrates Sufi spirituality into environmental education and daily routines, and the GreenFaith movement in the United States, an interfaith organization mobilizing religious communities for climate justice. Using a qualitative, interpretive phenomenological design, we collected interviews, observations, and documents across both contexts and analyzed them using a combined Heideggerian–Berger & Luckmann framework to trace how spiritual beliefs are translated into environmental norms. The findings revealed that both movements sacralize stewardship of the earth through theological principles such as tawhid (Oneness), khalifah (stewardship), and the interconnectedness of all creation, yet each followed a distinct pathway: pesantren privilege contemplative education and ritual practice, whereas GreenFaith foregrounded advocacy and public policy engagement. A translation chain, belief ritual → identity → action—emerged as the mechanism that connects spirituality to ecological activism. The study contributes to spiritual ecology by clarifying how embodied experiences and institutional processes co‑produce ecological meaning, identifying boundary conditions for education‑first versus advocacy‑first pathways, and highlighting the potential of faith‑based initiatives to support global environmental governance. Practical recommendations are offered for educators, policymakers, and interfaith leaders.